Haiti: The impact of COVID-19 and preliminary implications: Interim report - Díaz-Bonilla, Eugenio; Piñeiro, Valeria; De Salvo, Carmine Paolo; Laborde Debucquet, David (International Food Policy Research Institute, 2021)
The country is facing a damaging combination of political, economic, social, and health crises, playing out amidst extreme uncertainty. The current situation is to a large extent the continuation of a very complex political and social history. The more recent period opened after the ousting of the dictator JeanClaude Duvalier (known as Baby Doc) in 1986 and a sequence of military governments, when in 1990 Haiti had the first free election in modern history. The democratically elected president, Jean-Bertrand Aristide, was then driven from office by yet another military coup in 1991 but, after UN sanctions, free elections were again held in 1995. Concerns about security and the limitations of the fragile government to keep peace led to the establishment of the United Nations Mission in Haiti (UNMIH), a peacekeeping operation carried out between September 1993 and June 1996. The Mission was reestablished (MINUSTAH) in April 2004, after a rebellion took over most of Haiti and President Bertrand Aristide resigned. MINUSTAH ended in 2017, when it was replaced by a new UN compact (see below). Since 1995 there have been a sequence of free elections, but not without controversies and violence. In addition, the country suffered a series of very damaging natural disasters during this period, particularly the lethal earthquake of 2010 (from which Haiti has never fully recovered), but also a series of tropical storms and hurricanes (tropical storm Jeanne in 2004; hurricane Dennis in 2005; further tropical storms in 2008; hurricane Sandy in 2012; and hurricane Matthew in 2016, the strongest in decades). Recently, Haiti also experienced drought conditions that affected agricultural production. Furthermore, at the end of 2010 a cholera outbreak was reported, which ended up killing thousands of people, and whose source was a camp of UN peace-keeping soldiers.